Control of yeast gene expression by transposable elements: maximum expression requires a functional Ty activator sequence and a defective Ty promoter. - Coney, L R (1988)
Integration of a transposable element adjacent to a gene frequently results in an alteration in expression of the nearby gene. The purpose of our experiments was to identify cis-acting sequences within a yeast transposon (Ty) that are important for expression of the adjacent gene. The role of these sequences in Ty transcription was also analyzed in order to examine the relationship between Ty and adjacent gene expression. Three naturally occurring Ty elements located at the HIS4 locus were examined. These Ty elements differed by multiple sequence changes and had different effects on HIS4 expression. To determine which sequences were important to Ty and HIS4 expression, Ty::lacZ and Ty::HIS4::lacZ fusion genes were constructed and analyzed. Results of these experiments indicated that a sequence element is present in the Ty epsilon region that is necessary for HIS4 expression but which has only a modest effect on Ty transcription. Additionally, a mutation in the Ty promoter region decreased Ty transcription and increased HIS4 expression. The opposite effects of this mutation on Ty and adjacent gene expression were probably caused by promoter competition.